If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x-7)(3x+1)=(2x-5)(3x+2)
We move all terms to the left:
2(x-7)(3x+1)-((2x-5)(3x+2))=0
We multiply parentheses ..
2(+3x^2+x-21x-7)-((2x-5)(3x+2))=0
We calculate terms in parentheses: -((2x-5)(3x+2)), so:We multiply parentheses
(2x-5)(3x+2)
We multiply parentheses ..
(+6x^2+4x-15x-10)
We get rid of parentheses
6x^2+4x-15x-10
We add all the numbers together, and all the variables
6x^2-11x-10
Back to the equation:
-(6x^2-11x-10)
6x^2+2x-42x-(6x^2-11x-10)-14=0
We get rid of parentheses
6x^2-6x^2+2x-42x+11x+10-14=0
We add all the numbers together, and all the variables
-29x-4=0
We move all terms containing x to the left, all other terms to the right
-29x=4
x=4/-29
x=-4/29
| -4m^2+17m-15=0 | | 20+12x-10x-10=40 | | 0.11x=-0.36 | | -3(2w+5)+7w=5w(w-11) | | 3^x-4=6 | | 8x=4x-48 | | 2x+9=7x=6x | | 5+6a+18= | | 3^(x-4)=6 | | 5+6a+18=+a | | x+2=2×-3 | | -(8+12k)=2(8k-3) | | 7+3(y-8)=23 | | -½(x–6)=4 | | 900=j+309 | | 11x-4(3x-8)=37 | | 2(13x+18)=-23(x-4) | | –10t−4=2−9t | | 4(x-)=4x-5 | | 48*56=3*7*2c | | 5(10x+12)=-40(x-3) | | -5z+5=9 | | 6^(8x)=1.2^(11x+9) | | H=43+m | | 20(-12x+10)=38(x-2) | | 6/9=u/12u= | | 9+2(y-8)=24 | | 6^8x=1.2^11x+9 | | x+0.07x=22.90 | | (2x)°+(3x)°=90° | | 6/9=u/12= | | 54=12w-6w |